Revealing the path to a green economy: Insights and recommendations for sustainable development in Malaysia - Nik Athirah, Nik Mahdi; Fernando, Yudi; Azian, Ibrahim (Penerbit UTHM, 2024)
This study proposes a green economy framework leading to Malaysia's green economy roadmap and raising society's sustainability awareness. The framework has catered actionable insight into promoting a green economy to industrial sectors by integrating Environmental, social, and corporate governance (ESG) and Sustainable Development (SD) principles to improve Malaysia's achievement of Sustainable Development Goals (SDGs). This paper has critically analyzed a systematic review from 2209 journal articles indexed from two prominent databases, Scopus, and Web of Science. The data were analyzed using visualizing bibliometric networks and a computer-assisted qualitative method. The thematic pattern result was verified and strengthened using in-depth interviews with industrial business leaders. The result shows that establishing a green economy framework should align with a clear regulatory policy and incentives. This study provided a unique combination of proposing a green economy framework employing advanced analysis techniques and providing specific recommendations for the Malaysian context. Adopting the green economy framework led by integrated ESG, SD, and SDGs would lead to Malaysia's Shared Prosperity Vision 2030. The public listed companies should step ahead in adopting green economy frameworks